Adaptive heading control of unmanned wave glider with heading information fusion. (April 2019) - Leifeng, Wang; Ye, Li; Yulei, Liao; Kaiwen, Pan; Weixin, Zhang
Abstract: The unmanned wave glider (UWG) is a new kind of wave powered unmanned marine vehicle for persistent marine environment monitoring. However, the heading control of UWG is unusual, mainly about the heading control of the surface float body (Float), since it is indirectly actuated and with a large lag of the control response. The adaptive heading control method for the Float with heading information fusion is discussed. The basic and improved arrangement methods of the desired heading of Glider are proposed. Via direct heading control of Glider, the heading control of Float is realized indirectly. Simulation and sea trial results demonstrate that the proposed adaptive heading control method improves the heading control performance of UWG significantly. Highlights: The uniqueness of the heading control problem of UWG is analyzed. The basic and improved arrangement methods of the desired heading of Glider are proposed. Simulation and sea trial results verify the effectiveness of the proposed adaptive heading control method. The proposed adaptive heading control method improves the heading control performance of UWG significantly.